2017
DOI: 10.5430/ijhe.v6n3p99
|View full text |Cite
|
Sign up to set email alerts
|

Speaking in Tongues: Can International Graduate Students Read International Graduate Admissions Materials?

Abstract: A recent Educational Testing Services report (2016) found that international graduate students with a TOEFL score of 80-the minimum average TOEFL score for graduate admission in the United States-usually possess reading subscores of 20, equating to a 12 th -grade reading comprehension level. However, one public flagship university's international graduate student admissions instructions are written at a 17 th -grade reading comprehension level, or, a 27-30 band on the reading section of the TOEFL. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…Ultimately, this study's import—along with Taylor's () foundational work—renders any limitation relatively minor.…”
Section: Datamentioning
confidence: 98%
See 3 more Smart Citations
“…Ultimately, this study's import—along with Taylor's () foundational work—renders any limitation relatively minor.…”
Section: Datamentioning
confidence: 98%
“…This study aims to best triangulate the readability of each webpage by employing several commonly used readability measures in tandem and then averaging their results using Taylor's (2017aTaylor's ( , 2017b series. These readability measures include the Automated Readability Index (ARI) (Kincaid & Delionbach, 1973), the Flesch-Kincaid Grade Level Test (FK) (Kincaid, Fishburne, Rogers, & Chissom, 1975), the Gunning Fog Index (GFI) (Gunning, 1952) and the Simple Measure of Gobbledygook (SMOG) (McLaughlin, 1969).…”
Section: Eth Od Ologymentioning
confidence: 99%
See 2 more Smart Citations
“…Second, this study will learn whether 4-year institutions in the United States provide a machine translation widget or application on their institutional website so prospective Latina/o students can access admissions materials in their native language or the language spoken by individuals in their social networks, as these freely available machine technologies have been demonstrated to be nearly as accurate as humans when translating English to Spanish (Turner, 2016). Third, this study will reveal at what grade level undergraduate admissions materials are written—in both English and, if translated, Spanish—as recent research has suggested that many postsecondary materials are written above the 14th-grade English reading comprehension level (Taylor, 2017a, 2017b, 2018), although the average U.S. adult reads at the seventh-grade level (Clear Language Group, 2016).…”
mentioning
confidence: 99%